Pilot evaluation of horticultural therapy in improving overall wellness in veterans with history of suicidality. (June 2021) - Meore, Anne; Sun, Shengnan; Byma, Lauren; Alter, Sharon; Vitale, Amanda; Podolak, Evan; Gibbard, Brooke; Adams, Toby; Boyer, James; Galfalvy, Hanga; Yehuda, Rachel; Feder, Ann; et al.
Highlights: Horticultural therapy is effective in reducing risk factors of suicide in at-risk veterans. Horticultural therapy improves symptoms of stress, depression, pain and loneliness which are risk factors for suicidal ideation and behavior. A single dose of horticultural therapy appears to have a sustained effect in reducing symptoms of stress, depression, pain and loneliness. Abstract: Objectives: Novel approaches to mental health and suicide prevention are lacking. Converging evidence has shown the effectiveness of horticultural therapy (HT) in improving mental health symptoms, but whether it would reduce suicide risk and contributing risk factors is unknown. Design: Using a cohort model, HT was delivered 3.5 h over four weekly, sessions administered by a registered horticultural therapist to veterans with history of suicide ideation or attempt who felt isolated and experienced ongoing environmental stressors with interest in learning new coping strategies. Setting: HT delivery occurred in an urban garden, through a community partnership between the VA (Veterans Administration) and the New York Botanical Garden. Guided by principles of biophilia, participating veterans took part in nature walks, self-reflection and journaling, and planting activities. Outcome measures: Stress, mood, pain, and social isolation levels were measured weekly pre-post HT sessions using thermometer scales, with concordant validity to validated clinical instruments. Results: Of the 20 men and women with a history of suicide attempts/ideation, HT demonstrated immediate improvements after each session across all symptom domains in magnitude of reduction in stress, pain, mood, and loneliness. The effect sizes were in medium to large range (Cohen's d>.5). Additionally, a single HT session showed a sustained effect over subsequent 2-to-4 weeks as observed by the significantly decreased pre-session thermometer scores in subsequent weeks. Reductions in mood symptoms correlated with decline in suicidal ideation (rs = 0.63). Conclusion: HT intervention maybe a promising therapeutic modality for improving overall wellness in suicide prevention in at-risk veteran populations.